2022
DOI: 10.3390/ijms23052863
|View full text |Cite
|
Sign up to set email alerts
|

Application of High Throughput Technologies in the Development of Acute Myeloid Leukemia Therapy: Challenges and Progress

Abstract: Acute myeloid leukemia (AML) is a complex hematological malignancy characterized by extensive heterogeneity in genetics, response to therapy and long-term outcomes, making it a prototype example of development for personalized medicine. Given the accessibility to hematologic malignancy patient samples and recent advances in high-throughput technologies, large amounts of biological data that are clinically relevant for diagnosis, risk stratification and targeted drug development have been generated. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…AML is characterized by aberrant differentiation and abnormal clonal expansion of myeloid blasts ( Newell and Cook 2021 ; Xiang et al, 2022 ). It has been reported that dysregulated circRNAs can regulate cell differentiation, cell cycle progression and cell proliferation through acting as microRNA sponges in various diseases ( Xiao et al, 2021 ; Shi et al, 2022 ; Wang et al, 2022 ).…”
Section: Circrnas Regulte Cell Differentiation Cell Cycle Progression...mentioning
confidence: 99%
See 1 more Smart Citation
“…AML is characterized by aberrant differentiation and abnormal clonal expansion of myeloid blasts ( Newell and Cook 2021 ; Xiang et al, 2022 ). It has been reported that dysregulated circRNAs can regulate cell differentiation, cell cycle progression and cell proliferation through acting as microRNA sponges in various diseases ( Xiao et al, 2021 ; Shi et al, 2022 ; Wang et al, 2022 ).…”
Section: Circrnas Regulte Cell Differentiation Cell Cycle Progression...mentioning
confidence: 99%
“…AML has become a central research focus because it is the most common type of acute leukemia in adults worldwide, with rising morbidity and mortality ( Gallipoli et al, 2015 ; Liu et al, 2019 ; Bhattacharya and Gutti 2022 ). The key therapeutic strategies for AML include chemotherapy, allogenic hematopoietic stem cell transplantation and palliative care ( Xiang et al, 2022 ). However, although these advancements in the treatment of AML, the overall prognosis is poor (5-yeal overall survival only 28.7%) ( Singh V. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%